Adjuvant Osimertinib for Resected EGFR-Mutated Stage IB-IIIA Non–Small-Cell Lung Cancer: Updated Results From the Phase III Randomized ADAURA Trial. Issue 10 (1st April 2023) - Herbst, Roy S.; Wu, Yi-Long; John, Thomas; Grohe, Christian; Majem, Margarita; Wang, Jie; Kato, Terufumi; Goldman, Jonathan W.; Laktionov, Konstantin; Kim, Sang-We; Yu, Chong-Jen; Vu, Huu Vinh; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. PURPOSE: The phase III ADAURA (ClinicalTrials.gov identifier: NCT02511106 ) primary analysis demonstrated a clinically significant disease-free survival (DFS) benefit with adjuvant osimertinib versus placebo in EGFR-mutated stage IB-IIIA non–small-cell lung cancer (NSCLC) after complete tumor resection (DFS hazard ratio [HR], 0.20 [99.12% CI, 0.14 to 0.30]; P < .001). We report an updated exploratory analysis of final DFS data. METHODS: Overall, 682 patients with stage IB-IIIA (American Joint Committee on Cancer/Union for International Cancer Control, seventh edition) EGFR-mutated (exon 19 deletion/L858R) NSCLC were randomly assigned 1:1 (stratified by stage, mutational status, and race) to receive osimertinib 80 mg once-daily or placebo for 3 years. The primary end point was DFS by investigator assessment in stage II-IIIA disease analyzed by stratified log-rank test; following early reporting of statistical significance in DFS, no further formal statistical testing was planned. Secondary end points included DFS in stage IB-IIIA, overall survival, and safety. Patterns of recurrence and CNS DFS were prespecified exploratory end points. RESULTS: At data cutoff (April 11, 2022), in stage II-IIIA disease, median follow-up was 44.2 months (osimertinib) and 19.6 months (placebo); the DFS HR was 0.23 (95% CI, 0.18 to 0.30); 4-year DFS rate was 70% (osimertinib) and 29% (placebo). In the overall population, DFS HR was 0.27 (95% CI, 0.21 to 0.34); 4-year DFS rate was 73% (osimertinib) and 38% (placebo). Fewer patients treated with osimertinib had local/regional and distant recurrence versus placebo. CNS DFS HR in stage II-IIIA was 0.24 (95% CI, 0.14 to 0.42). The long-term safety profile of osimertinib was consistent with the primary analysis. CONCLUSION: These updated data demonstrate prolonged DFS benefit over placebo, reduced risk of local and distant recurrence, improved CNS DFS, and a consistent safety profile, supporting the efficacy of adjuvant osimertinib in resected EGFR-mutated NSCLC.